Pengaruh Pemberian Pisang Terhadap Kadar CK-MB Dan Sel Darah Putih Pada Mahasiswa Sebelum Dan Sesudah Olahraga - Dini Puspodewi; Yusuf Eko Nugroho; Wishnu Subroto (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Bananas are a natural source of carbohydrates and potassium that are commonly consumed as an energy supply before physical activity. Their nutritional content is thought to help maintain metabolic stability during exercise, yet their influence on cardiac biomarkers and immune responses remains unclear. This study aimed to determine the effect of banana consumption on Creatine Kinase-MB (CK-MB) levels and white blood cell counts in students before and after exercise. This research employed a pre- and post-test design involving 15 randomly selected students from the Medical Laboratory Technology Program at Universitas Al-Irsyad Cilacap. Blood samples were collected before and after exercise under two conditions: without banana consumption and after consuming bananas. CK-MB levels were measured using a photometer, while leukocyte counts were analyzed using a hematology analyzer. Paired t-test results showed no significant differences in CK-MB levels before and after exercise (p > 0.05), although a slight increase in mean values was observed within physiological limits. Similarly, there was no significant difference in leukocyte counts following exercise (p > 0.05), with the effect size categorized as very small for both variables. These findings indicate that consuming bananas prior to exercise does not significantly affect cardiac biomarkers or inflammatory responses in students performing light-to-moderate physical activity. Bananas remain safe to consume before exercise and can serve as an energy source without causing notable physiological changes.